Calotes versicolor (Squamata: Agamidae)—A New Invasive Squamate for Borneo - Das, Indraneil; Charles, Joseph K.; Edwards, David S. (The Herpetological Society of Japan, 2008)
Calotes versicolor, hitherto known from the Asian mainland, from eastern Iran, across the Indian Subcontinent, to Indo-China and Indo-Malaya, with several naturalized populations in both the New and Old Worlds, is here reported for the first time from Borneo (from Brunei Darussalam, in the northwestern part of the island). The ecological consequences of invasion of this agamid lizard, reported from studies elsewhere, include competition with other saurian species, and predation on local invertebrates and small vertebrates, with undesirable effects in terms of conservation of the local biota.